PENGARUH MOTIVASI DAN BUDAYA ORGANISASI TERHADAP PRODUKTIFITAS KERJA KARYAWAN ( STUDI KASUS DI PT BOOGI AVINDO, BOGOR) - Arif Prayogo (Majalah Ilmiah Bijak, 2016)
This study was taken from the thesis research aims to analyze how much Influence Motivation and Cultural Organization on labor productivity Employees (Case Study in PT Boogi Avindo, Bogor). The study is based on the phenomenon, which showed a decrease in employee productivity, one of them due to low employee motivation, and poor corporate cultureThe sampling method used is simple random sampling. The sample in this study followed the formula Slovin, or as many as 35 employees.Data that has met the test of validity and reliability further processed to produce a regression equation 0.242+ 0286 X1 + 0.699 X2, where Y is the variable Employee Productivity, Motivation X1 and X2 are the variables are variables Organizational Culture. Hypothesis testing using t test showed that each of the independent variables studied was shown to significantly affect the dependent variable partially on Employee Productivity. Motivation partially positive effect on Work Productivity indicated by the r value of 0815 which means a strong relationship between them. Organizational culture is partially positive effect on Work Productivity indicated by the r value of 0.747, which means a strong relationship between them. Motivational variables simultaneously and Cultural Organization has a significant influence on Work Productivity indicated by the r value of 0.776 which means the relationship between them is very strong. While the value of the coefficient of determination (R2) is equal to 0.602, which means that motivation together with Cultural Organization may explain the variable Work Productivity by 60, 2%, while the remaining 39.8% is explained by other variables.